Could tannins be the right dietary alternative for replacing antibiotics as growth promoters in broiler chicken production? A comprehensive microbiota shift assessment in a commercial farm - Natalia Pin Viso; Enzo Redondo; Leandro Redondo; Juan Díaz Carrasco; Marisa Farber; Mariano Fernández Miyakawa (Poultry Science)
One of the main global issues in animal production is the antimicrobial use (AMU) as prophylactic additives in diet. Despite the availability of a variety of antibiotic alternative additives, their use is not widespread. In this study, we analyzed samples from a trial conducted on a commercial farm, evaluating cecal and litter microbiota with the inclusion of antibiotics or tannins (as AMU-free alternative) in the diet. We observed differential modulation depending on the additive used. Specifically, tannins treatment led to an increased Firmicutes/Bacteroidetes ratio, due to a rise in Clostridiales order, which is associated with improved gut health and better energy efficiency in birds. Poultry litter microbiota contained typical gastrointestinal tract bacteria, along with pathogenic and environmental species. This information becomes relevant for litter reuse in poultry sheds, acting as an inoculum for new birds in the next cycle, determining their microbiota; or when litter is used as organic fertilizer, and these bacteria potentially spread to the environment. This study highlights the potential of tannins as a promising AMU-free alternative in food-producing animals, contributing to new productive paradigms that consider human health, animal welfare, environmental impact, and production efficiency.